The Effect of Erosional Transformation of Soil Cover on the Stability of Soil Aggregates within Young Hummocky Moraine Landscapes in Northern Poland - Hanna Radziuk; Marcin Świtoniak (Agronomy, 2022)
Aggregate stability is a crucial factor in predicting the development of the erosion process, and it is particularly important in landscapes with high heterogeneity of soil cover, such as young hummocky moraine uplands. The objective of the presented work was to estimate the influence of erosion on the properties of aggregates and analyze the variation of aggregate stability under different erosion-related alterations of soil cover. The conducted research indicates that erosion has led to a deterioration of the quality of soil structure in the upper parts of the slopes, which in turn may intensify the slope processes leading to faster truncation of the pedons. Both the differentiation of the soils themselves and the stability of the aggregates were very strongly linked to erosive transformations. The tops of the hills and the upper parts of the slopes are covered with completely or strongly eroded soils in which the aggregates have the least favorable characteristics. Due to the smallest amount of humus and the highest clay content, the soils have the largest share of soil clods, which are aggregates larger than 7 mm that may have formed in dry conditions (soil drought). The plow horizons of most eroded Eutric Regosols and strongly eroded Luvisols have very poor water resistance, similar to that of the subsoils. The main factor determining the low aggregate stability of Eutric Regosols is the number of secondary carbonates that lead to a rise in soil dispersion. Strongly eroded Haplic Luvisols have a low resistance to water due to relatively high clay content (20–26 percent). The higher stability of aggregates in soils with colluvial materials (Albic Luvisols, Mollic Gleysols, Endogleic Phaeozems) depends mainly on soil organic carbon content. The results showed the necessity for adaptation of land management practices to real condition and heterogeneity of soil cover.